If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -4z = -2z + 9 Reorder the terms: 13 + -4z = 9 + -2z Solving 13 + -4z = 9 + -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. 13 + -4z + 2z = 9 + -2z + 2z Combine like terms: -4z + 2z = -2z 13 + -2z = 9 + -2z + 2z Combine like terms: -2z + 2z = 0 13 + -2z = 9 + 0 13 + -2z = 9 Add '-13' to each side of the equation. 13 + -13 + -2z = 9 + -13 Combine like terms: 13 + -13 = 0 0 + -2z = 9 + -13 -2z = 9 + -13 Combine like terms: 9 + -13 = -4 -2z = -4 Divide each side by '-2'. z = 2 Simplifying z = 2
| 0.5(8n-2)=16-30n | | 6.1=y-9.5 | | 5x+19=13x-53 | | -8=h-3 | | w^2-12w+31=0 | | 4x+27=6x+11 | | v-33=23 | | 2x+10=74-6x | | 20x+27= | | -3-3(t-3)=-5(t+4)+4 | | 5(x-2)=2x-(6-x) | | 43*.2+x*.65=60 | | -5x+2(2x-2)=3-8x | | 2x-2=9x-25 | | -2(y-2)=7(5-y)-9 | | 0.09+3.6=1.44 | | 2371.7+0.31(m-10570)=34597 | | x+(x+1)+(x+2)=36 | | 5=3x+4 | | 2x+1-6=3+x | | 9p=8(9p+7) | | 9w=54 | | -3(y-6)=5(3-y)-7 | | 5x-(2x+2)=x+(3x-5) | | 6x-90=4x | | 4x-(3x-1)=2 | | -10c=-60 | | 16=3(x-1)-(x-7) | | 2a+9=17-3a | | ax^2-20x+40=0 | | -10=-60 | | x^4+3x^3=24-18x-2x^2 |